The relationship between the manners of parenting by parents and the extent of anxiety among the students - Reza Rezaei; Nader Noori; Ali Rezaei; Ahmad Fotoohi; Ali Mohammadvali (Chronic Diseases Journal, 2018)
BACKGROUND: Mental health among the children and adolescents is an essential part of public welfare and health. The transfer of values and culture, and children health are made via training. According to conducted studies, training style of parents is an important factor to predict the health problems among the children. Baumrind has conducted extensive researches on the manner of parenting. He recognized three manners of parenting, authoritative, authoritarian, and permissive. These are different from each other in terms of control, and being hot. The aim of this research was to study the relationship of parenting manners of parent and the extent of anxiety among the students.